2015
DOI: 10.1016/j.jqsrt.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Hartmann–Tran profile to precise experimental data sets of 12C2H2

Abstract: Self-and nitrogen-broadened line shape data for the P e (11) line of the ν 1 + ν 3 band of acetylene, recorded using a frequency comb-stabilized laser spectrometer, have been analyzed using the Hartmann-Tran profile (HTP) line shape model in a multispectrum fitting. In total, the data included measurements recorded at temperatures between 125 K and 296 K and at pressures between 4 and 760 Torr. New, sub-Doppler, frequency comb-referenced measurements of the positions of multiple underlying hot band lines have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In this particular case, it was shown [181] that the ratio of the broadening speed-dependence parameter to the pressure-broadening coefficient should be independent of T. This result was experimentally confirmed to within a few percent for variable-temperature measurements of CO 2 line shapes in the 1.6 m region [181]. However, some other experimental studies [103,[182][183][184] have shown that the temperature dependences of the line broadening and of its quadratic speed-dependent component are significantly different. For the Dicke-narrowing parameter (generally denoted by  VC ), a power law for its temperature dependence was used in a few studies (eg [103,182,185,186]) that have investigated this issue.…”
Section: 24b Temperature Dependence Of the Line-shape Parametersmentioning
confidence: 60%
“…In this particular case, it was shown [181] that the ratio of the broadening speed-dependence parameter to the pressure-broadening coefficient should be independent of T. This result was experimentally confirmed to within a few percent for variable-temperature measurements of CO 2 line shapes in the 1.6 m region [181]. However, some other experimental studies [103,[182][183][184] have shown that the temperature dependences of the line broadening and of its quadratic speed-dependent component are significantly different. For the Dicke-narrowing parameter (generally denoted by  VC ), a power law for its temperature dependence was used in a few studies (eg [103,182,185,186]) that have investigated this issue.…”
Section: 24b Temperature Dependence Of the Line-shape Parametersmentioning
confidence: 60%
“…The details of the RP and GP calculations can be found in the paper by Wang et al [30]. HTP was calculated according to Forthomme et al [31], who provide the Matlab implementation as a supplement to the paper.…”
Section: Experimental Results and Modelling Of The H2 Lineshapementioning
confidence: 99%
“…The temperature dependences of the pressure broadening and shifting parameters are usually described by a power law and a linear function (see Gordon et al, , and references therein), respectively. For the higher‐order parameters, their temperature dependences have been investigated only in a few studies (e.g., Forthomme et al, ; Goldenstein & Hanson, ; Li et al, ; Wilzewski et al, ). These studies showed that Γ 2 ( T ) and ν vc ( T ) as well as ζ ( T ) can be described by a similar power law as for the line broadening.…”
Section: Spectra Analysis and Resultsmentioning
confidence: 99%